Efficacy of Sodium Hyaluronate for Temporomandibular Joint Disorder by Single-Puncture Arthrocentesis - Sequeira, Joyce (J Maxillofac Oral Surg, 2018)
BACKGROUND: The term temporomandibular joint internal derangement has characteristic clinical findings such as restricted mouth opening, pain, irregular deviated jaw function and clicking sounds. The technique of TMJ arthrocentesis has gained widespread acceptance as a simple and effective technique for the treatment of acute persistent closed lock of the TMJ. Arthrocentesis is known as the lavage and lysis of upper joint compartment. PURPOSE: To evaluate the efficacy of sodium hyaluronate followed by single-puncture arthrocentesis. Sodium hyaluronate is the sodium salt of hyaluronic acid which is a polysaccharide of the glycosaminoglycans family, found in many extracellular tissues, including synovial fluid and cartilage. Exogenous hyaluronate can stimulate the synthesis of endogenous hyaluronic acid. METHODS: In our study, a sample of 10 patients (7 females and 3 males) with TMJ disorder was selected. Arthrocentesis was done followed by sodium hyaluronate injection for all the patients. RESULTS: On follow-up ranging from 1 to 3 months, pain at rest and pain on mastication had substantially decreased in all patients and mandibular function and mouth opening had significantly improved. CONCLUSION: Our study shows that single-puncture Ringer’s lactate arthrocentesis followed by sodium hyaluronate injection is effective in the management of the internal derangement of the temporomandibular joint.